Preoperative level of serum amyloid A is superior to C‐reactive protein in the prognosis of esophageal squamous cell carcinoma. Issue 7 (30th August 2013) - Meng, Y. Q.; Cao, X.; Wen, Z. S.; Liu, Q. W.; Tan, Z. H.; Duan, H.; Ma, G. W.; Lin, P.
Summary Preoperative elevations in the levels of serum amyloid A (SAA) or C‐reactive protein (CRP) have been reported to be prognostic indicators in several malignancies. The aim of this study is to evaluate the serum levels of SAA and CRP in the prognosis of esophageal squamous cell carcinoma (ESCC). In total, 252 patients with ESCC who had undergone surgery with curative‐intent were retrospectively recruited. The specificity, sensitivity, and prognostic value of SAA or CRP levels were measured as the area under the receiver operating characteristic (ROC) curve (AUC). The clinical value of SAA and CRP levels as prognostic indicators was evaluated using Cox's proportional hazards model. The 1‐, 3‐, and 5‐year overall survival (OS) rates for the entire cohort of patients with ESCC were 71.0%, 61.0%, and 43.0%, respectively. The correlation between the levels of SAA and CRP was significant (r2 = 0. 685, P < 0.001). The ROC analysis showed that the levels of CRP were associated with a significantly lower overall accuracy than were the SAA levels (AUC, 0.615 vs. 0.880; P < 0.001). For the complete cohort, the median OS was 52.0 months longer in patients with low preoperative serum levels of SAA (72.0 months) compared with patients who had high SAA levels (20.0 months, P < 0.001). The median OS among patients with low CRP levels was also longer compared with the patients who had high CRP levels (72.0 vs. 51.0 months, respectively; P < 0.001). Subgroup analyses showed that the preoperative elevated levels of SAA could find significant differences in OS for stage I, stage II, and stage III (P < 0.001, P = 0.001, and P < 0.001, respectively), whereas the increased levels of CRP could only find a difference in OS for stage II cancers. After a multivariate analysis, preoperative elevated level of SAA was found to be an independently and significant prognostic factor (P < 0.001). Our study indicates that the preoperative levels of SAA and CRP can act as prognostic factors, and that elevated levels of these proteins are associated with negative effects on the survival of patients with ESCC. SAA showed a higher prognostic value than CRP in both cohort and subgroup analysis.